Should the CDC's recommendations for promptly removing unnecessary centrally inserted central catheters be enhanced? Ultrasound-guided peripheral venous cannulation to fully comply - Iordanou, Stelios; Middleton, Nicos; Papathanassoglou, Elizabeth; Palazis, Lakis; Raftopoulos, Vasilios (My University, 2020)
In an effort to reduce catheter-related bloodstream infection's incidence rates in an intensive care unit, several evidence-based procedures recommended by the Centers for Disease Control and Prevention for centrally inserted central catheters were implemented. A failure to fully comply with the recommendation for prompt removal of the centrally inserted central catheters was attributed, mainly to the difficulties and inadequacies raised from establishing peripheral venous access.
Keywords: Centers for Disease Control and Prevention; Bloodstream infection; Catheter-related bloodstream infection; Central venous catheter; Centrally inserted central catheters; Intensive care; Peripheral venous access; Ultrasound